The right to the ecological city: Reconciling ecological sustainability and social justice in a neighbourhood transformation in Turin - Karl Krähmer (PlaNext, 2025)
Cities have gained increasing attention in the debate on how to tackle the global environmental crisis. However, urban strategies for sustainability have often been criticised for being insufficient in effectively mitigating environmental impacts due to externalisation and cost-shifting, and for producing social contradictions, such as ecological gentrification. Rather than considering these critiques as reasons to abandon ecological urban transformations, this article advocates for the right to the ecological city, for which the goals of ecological sustainability and social justice need to be reconciled through a degrowth strategy based on the principles of sufficiency, reuse and sharing. However, this theoretical framework encounters several challenges in urban practice. These are discussed through the author’s lens as an observant participant in the Fondazione di Comunità Porta Palazzo, a community foundation involved in the transformation of the neighbourhoods of Aurora and Porta Palazzo in Turin, Italy, through projects focused on public space and housing. The discussion of these challenges suggests that while the right to the ecological city is hard to achieve, it remains an important goal in the transformation of cities and neighbourhoods, one that must rely on structural change driven by diverse actors across multiple scales.